2022
DOI: 10.1186/s40359-022-00759-y
|View full text |Cite
|
Sign up to set email alerts
|

Mental health and self-determination profiles of the diverse population of medical students in Malaysia during the COVID-19 pandemic

Abstract: Introduction Medical schools throughout the world were forced to modify their programming during the COVID-19 pandemic. In Malaysia, virtual learning plans were implemented for non-clinical programming, while clinical posting modifications were designed to meet local SOPs. The prolonged enforcement of these modifications to undergraduate medical education will have affected student experiences, including well-being. Since these feelings can relate to perceived relatedness, autonomy, and compete… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…Studies during the COVID-19 pandemic reported students feeling lonely and not being able to communicate with teaching staff and their peers as frequently as they would like [16]. However, our study found that students enrolled on courses delivered predominantly inperson could also experience loneliness, because the VLE's flexibility could create, or even be used to create, barriers between students, teaching staff, and peers.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Studies during the COVID-19 pandemic reported students feeling lonely and not being able to communicate with teaching staff and their peers as frequently as they would like [16]. However, our study found that students enrolled on courses delivered predominantly inperson could also experience loneliness, because the VLE's flexibility could create, or even be used to create, barriers between students, teaching staff, and peers.…”
Section: Discussionmentioning
confidence: 53%
“…Course-related environmental factors such as workload, assessment stress, lecturers' support for student autonomy, peer relationships, and feelings of belonging have been found to have a greater association with student mental wellbeing compared to factors such as concern about finances, English language skills, or future employment [14]. The sudden shift to online learning because of the COVID-19 pandemic generated worldwide interest in the wellbeing of university students in online environments, where courses are delivered 80-100 percent online, e.g., in Canada, Malaysia, and India [15][16][17]. However, to our knowledge, little research has focused on the impact on students' mental wellbeing from online learning environments used for courses delivered in-person and on-campus [18].…”
Section: Introductionmentioning
confidence: 99%
“…COCKBURN et al ( 2022), a study of medical students during the pandemic, observed that female students had significantly worse mental health [34]. PEDRAZ-PETROZZI et al (2021) studied 375 people, including health care professionals and medical students, and demonstrated that being female and younger were associated with pandemic-related depression and stress, in addition to being frontline personnel [35].…”
Section: Discussionmentioning
confidence: 99%
“…They used a single questionnaire with twelve items (GHQ-12) and showed that the pandemic led to psychological distress, which was more significant in females than in males (Idowu et al, 2022). COCKBURN et al (2022), in a study of medical students during the pandemic, observed that female students had significantly worse mental health (Cockburn et al, 2022). PEDRAZ-PETROZZI et al (2021) studied 375 people, including health care professionals and medical students, and demonstrated that being female and younger were associated with pandemic-related depression and stress, in addition to being frontline personnel (Pedraz-Petrozzi et al, 2021).…”
Section: Discussionmentioning
confidence: 99%